2023
DOI: 10.3390/foods12122364
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment and Ripeness Prediction of Table Grapes Using Visible–Near-Infrared Spectroscopy

Abstract: Ripeness significantly affects the commercial values and sales of fruits. In order to monitor the change in grapes’ quality parameters during ripening, a rapid and nondestructive method of visible–near-infrared spectral (Vis-NIR) technology was utilized in this study. Firstly, the physicochemical properties of grapes in four different ripening stages were explored, with increasing color in redness/greenness (a*) and Chroma (C*) as well as soluble solids (SSC) content as ripening advanced, and decreasing values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Passion fruit is a leapfrog fruit, and its internal biological processes (e.g., respiration and transpiration) result in water loss during storage. Throughout the preservation process, the passion fruit pericarp endures substantial dehydration, with water loss occurring predominantly in the pericarp rather than in the pulp [ 13 ]. Plant cell break caused by this phenomenon is a key factor contributing to the variations in hardness during storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passion fruit is a leapfrog fruit, and its internal biological processes (e.g., respiration and transpiration) result in water loss during storage. Throughout the preservation process, the passion fruit pericarp endures substantial dehydration, with water loss occurring predominantly in the pericarp rather than in the pulp [ 13 ]. Plant cell break caused by this phenomenon is a key factor contributing to the variations in hardness during storage.…”
Section: Resultsmentioning
confidence: 99%
“…They evaluated two spectroscopic systems, and the findings suggested a somewhat improved measuring performance for NIRS system, with the best correlation [ 12 ]. Fengjiao Ping et al have effectively constructed excellent spectrum models by investigating grape hardness and other physicochemical properties, thus providing a valuable technique for quick, non-destructive detection in measuring grape maturity, enhancing quality control [ 13 ]. These case studies further support the viability and accuracy of NIRS technology in measuring fruit hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Rouxinol et al [14] also report high R 2 values for • Brix (0.86) and TA (0.86) in red grape varieties using the 1100-2300 nm spectral range. Finally, Ping et al [16], using the table grape variety Kyoto, reported R 2 of 0.92 and RMSE of 1.01 for • Brix, and R 2 of 0.94 and RMSE of 1.78 for TA.…”
Section: Discussionmentioning
confidence: 96%
“…Along the same line, Daniels et al (2019) [15] explored the use of NIR spectroscopy to quantify total soluble solids (TSS), TA, TSS/TA, and pH non-destructively on intact bunches, achieving promising results using the Partial Least Squares (PLS) algorithm. Ping et al (2023) [16], by using the VNIR spectra, estimated the soluble solid content (SSC) and TA of the grapes, also recording the changes in the chemical composition at different maturity levels. The Vis, NIR, and SWIR spectroscopy was also explored by Meja-Correal et al (2023) [17] for grape TSS estimation by applying a PLS regression model and selecting the best spectral range to avoid complex and potentially overfitted regression models, concluding that the most suitable spectral range for TSS predictions was the NIR range (701-1000 nm).…”
Section: Introductionmentioning
confidence: 99%